A Patient with Uncontrollable Belching: What to Do? - I. V. Maev; Yu. A. Kucheryaviy; E. V. Barkalova; M. A. Ovsepyan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Aim. In this paper, we discuss the clinical significance of belching and present a clinical case with the description of the belching differential diagnosis.Main findings. Belching may be either a physiological or a pathological phenomenon. Pathological belching requires an adequate diagnostic approach in order to clarify the nature of its occurrence. Gastric belching occurs reflexively at the moment of stomach stretching by excess air trapped during swallowing, which initiates the transient relaxation of the lower esophageal sphincter. As a consequence, the swallowed air escapes from the stomach first into the esophagus and then into the throat. Supragastric belching is a phenomenon, in which the air entering the esophagus does not reach the stomach, but rapidly returns to the throat. In this case, unlike aerophagia, the air entering the esophagus is not accompanied by the act of swallowing. Supragastric belching is not a reflex process; rather, it is considered to be a manifestation of behavioural disorders. 24-hour pH-impedancemetry and high-resolution esophageal manometry are highly informative methods for detecting various types of belching (gastric and supragastric), as well as their mechanisms. We present a clinical observation of a 47-year-old patient suffering from supragastric belching and treated by speech therapy under the supervision of a speech therapist. Conclusion. 24-hour pH-impedancemetry and high-resolution esophageal manometry (also in combination with impedancemetry) provide a complete differential diagnosis of belching and allow the most effective patient management strategy to be selected.